Analysis of the subject field of the phenomenon of communicative culture in dissertation research on pedagogical science - Valentina G. Ryndak; Yuliya A. Bazhenova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper is devoted to the phenomenon of communicative culture in pedagogical science. The material for the study was the domestic dissertation research on pedagogy from 1998 to 2017, the subject of which is this phenomenon. The authors define the main theoretical constructs (communicative competence, pedagogical communication, communication culture, etc.), which allowed researchers to formulate their own definition of the phenomenon of communicative culture. It is revealed that the performances of modern domestic scientists understanding of the studied phenomena is ambiguous and depends on the specific problems of the study, in 53.1% of studies, the phenomenon of communicative culture is understood as an integral (or integrative) personal quality; 9.5% - as a component of professional activity, giving the opportunity to represent the studied phenomenon by transferring characteristics of professional activity; in 16.6 per cent as the quality of the individual, reflecting the motives and needs of communication and interaction with other people; in 20.2% - as the ability to establish a variety of social contacts, depending on the mastery of science and the art of communication, patterns and values of behavior. At the same time, related concepts (for example, communicative activity, pedagogical communication, communicative competence, culture of communication, etc.) were studied in detail. Freedom in determining the components of the structure of the phenomenon of communicative culture, we explain the artificiality of ideas about it in the mind of the researcher as a consequence of transposition (a variant of the result of generalization).